2022
DOI: 10.1021/acsaem.2c01352
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Color Semiconductors: Methylamine Intercalation, Deintercalation, and Retention in Two-Dimensional Halide Perovskites

Abstract: The low formation energy of metal halide perovskites (MHPs) and their high performance in optoelectronic applications make them rather interesting semiconductor materials. In this work, we take advantage of the tunability of two-dimensional (2D) halide perovskites of the type A2PbI4 to explore a chromogenic mechanism in these materials where methylamine is allowed to intercalate into and deintercalate from the halide perovskite films. Methylamine intercalation results in a change in color from the initial yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In 2022, Surel et al reported the initial discovery that the yellow PEA 2 PbI 4 (PEA = C 6 H 5 C 2 H 4 NH 3 + ) film underwent a transition to the colorless state upon exposure to CH 3 NH 3 vapor, and reverted back to its original state upon removal of the CH 3 NH 3 vapor (Figure 8a). [94] This color switch phenomenon was also observed in a series of RP-type 2D perovskites by substituting the A site with a series of phenalkylammonium cations. They provided an explanation film upon exposure and removal to CH 3 NH 3 .…”
Section: D Thermochromic Perovskitesmentioning
confidence: 66%
See 2 more Smart Citations
“…In 2022, Surel et al reported the initial discovery that the yellow PEA 2 PbI 4 (PEA = C 6 H 5 C 2 H 4 NH 3 + ) film underwent a transition to the colorless state upon exposure to CH 3 NH 3 vapor, and reverted back to its original state upon removal of the CH 3 NH 3 vapor (Figure 8a). [94] This color switch phenomenon was also observed in a series of RP-type 2D perovskites by substituting the A site with a series of phenalkylammonium cations. They provided an explanation film upon exposure and removal to CH 3 NH 3 .…”
Section: D Thermochromic Perovskitesmentioning
confidence: 66%
“…Reproduced with permission. [ 94 ] Copyright 2022, American Chemical Society. b) FAX stripping induced thermochromism of 2D RP‐type perovskite.…”
Section: Chromic Perovskite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat unique to MHPs is the range of mechanisms which provide large changes in transmission, with some material compositions exhibiting several different chromogenic mechanisms. To date, the mechanisms investigated include thermally driven crystal phase transformations, 41,42 hydration [43][44][45] or complexation with other intercalant molecules, [46][47][48][49][50][51][52] changes in structural dimensionality, 53 and other mechanisms besides. 54 This wide range of mechanisms and stimuli has led researchers to imagine many other applications beyond color changing photovoltaic windows, 46,54,55 but those most relevant to windows are discussed here.…”
Section: Switchable Pscsmentioning
confidence: 99%
“…This expansion/contraction can lead to signicant morphological changes aer very few color change cycles. 50,52 Both of these instabilities remain challenging, but work is being done to template both materials 52 and device structures 62 to help relieve these stresses and offer improved device lifetime. Because of these two issues, while it addresses many aspects necessary for switchable photovoltaic windows, this switching mechanism's particular stability issues are likely to be a major hurdle to its development into a product.…”
Section: Technology Outlookmentioning
confidence: 99%